Onion tears : a novel - Khan, Shubnum (New Delhi : Penguin Books, 2011)
Loss and life are the themes that weave through this tale of three generations of Muslim women living in suburban South Africa. Khadeejah Bibi Ballim is a hard-working and stubborn first-generation Indian who longs for her beloved homeland and often questions what she is doing on the tip of Africa. At thirty-seven, her daughter Summaya is struggling to reconcile her South African and Indian identities, while Summaya s own daughter, eleven-year-old Aneesa, is a girl who has some difficult questions of her own. Is her mother lying to her about her father s death? Why won t she tell her what really happened? Gradually, the past merges with the present as the novel meanders through their lives, uncovering the secrets people keep, the words they swallow and the emotions they elect to mute. For this family, faintly detectable through the sharp spicy aromas that find their way out of Khadeejah s kitchen, the scent of tragedy is always threatening. Eventually it may bring this family together, if not, it will tear them part.
Novel.
Keywords: Muslim women -- South Africa -- Fiction